2013
DOI: 10.1093/ejcts/ezt557
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical outcomes of robot-assisted surgery for anterior mediastinal mass: its superiority over a conventional sternotomy approach evaluated by propensity score matching†

Abstract: In carefully selected patients with relatively smaller sized masses, robot-assisted surgery resulted in excellent early clinical outcomes with lesser tube drainage, lower blood loss, shorter tube days and length of hospital stay without any postoperative complications, compared with the matched open group. Further investigation for long-term clinical outcomes and oncological outcomes is required for a robotic approach. Particularly, long-term follow-up for the local recurrence rate according to the pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 20 publications
1
84
0
1
Order By: Relevance
“…Seong et al also reported a propensity-matched analysis comparing robotic and conventional sternotomy approaches for anterior mediastinal mass resection. 33) They concluded that robotic surgery resulted in better outcomes including less tube drainage, lower blood loss, shorter tube days, length of hospital stay, and less complication rates. Melfi et al reported long-term experiences of mediastinal robotic surgery with no intraoperative complications and no mortality.…”
Section: Mediastinal Tumormentioning
confidence: 99%
“…Seong et al also reported a propensity-matched analysis comparing robotic and conventional sternotomy approaches for anterior mediastinal mass resection. 33) They concluded that robotic surgery resulted in better outcomes including less tube drainage, lower blood loss, shorter tube days, length of hospital stay, and less complication rates. Melfi et al reported long-term experiences of mediastinal robotic surgery with no intraoperative complications and no mortality.…”
Section: Mediastinal Tumormentioning
confidence: 99%
“…Approximately 85% of patients with liposarcoma of the thoracic cavity have complaints pertaining to the tumor, while 15% are asymptomatic and present incidentally on chest radiography. 5 Surgical resection is the mainstay of anterior mediastinal tumors and a median sternotomy is regarded as the conventional approach to surgical resection of anterior mediastinal masses. Seong et al found out that robotic resection of anterior mediastinal masses was associated with less haematocrit drop and was linked to shorter hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…They recommended that robotic -assisted surgery be utilized in the surgical management of smallsized anterior mediastinal masses. 5 Careful anesthetic management of the obese patient with a pulmonary pathology plays an immense role in the surgical outcomes of these patients. Their multiple comorbidities such as metabolic syndrome and obstructive sleep apnea puts them at high risk of airway obstruction and cardiovascular collapse during Induction of general anesthesia and intra-operatively (6 -8).…”
Section: Discussionmentioning
confidence: 99%
“…Early outcomes of robot-assisted surgery for the anterior mediastinum performed in South Korea were reported by Seong et al (25). Propensity score matching was done to compare with a thoracotomy, which revealed a lower number of drains, lower 24-hour tube drainage amounts, less hemoglobin loss, fewer chest tube days, and shorter length of hospital stay in the robotic group.…”
Section: Robot-assisted Thoracoscopic Surgery For Thymic Diseases In mentioning
confidence: 95%